Space-Time Dynamics of Fertility and Commuting - Elena Kotyrlo (European Regional Science Association (ERSA), 2014)
The study contributes in analytical description of spatial diffusion of fertility, in particular, influenced by labour movements of people between places of residence and work. It is assumed that the labour market has externality on the marriage market due to commuting, which, in turn, affects fertility. The analytical model, decomposing spatial interaction of fertility and commuting, is constructed on the base of a model of the demand for children, spatial stock-flow model, and a matching model of a marriage market with a sex ratio as the probability of matching. Empirical evidence on municipal Swedish data for the period 1994-2008 does not provide any strong evidence of spatial diffusion of fertility. However, externalities of labour mobility on fertility due to changes of gender structure of population are not rejected.
Keywords: J13; C23; 330